PHENOLIC CONSTITUENTS FROM SARCOPYRAMIS NEPALENSIS AND THEIR Α-GLUCOSIDASE INHIBITORY ACTIVITY - Tan, Chao; Zuo, Jiangcheng; Yi, Xiaofang; Wang, Peng; Luo, Chunhua; Hu, Yong; Yi, Hong; Qiao, Wei (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: This study was carried out to fully investigate the phenolic chemical constituents of Sarcopyramis nepalensis and determine their α-glucosidase inhibitory activity. Materials and Methods: S. nepalensis was extracted using the ultrasonic assistant extraction (UAE) method and further fractionated with petroleum ether (PE), chloroform (CHCl3), ethyl acetate (EtOAc) and n-butanol (n-BuOH), respectively. The active fraction was chromatographed on AB-8 macroporous resin column, silica gel column, Sephadex LH-20 column, RP-ODS column and semi-preparative HPLC column. The isolated phenolic constituents were identified by 1H-Nuclear Magnetic Resonance (NMR), 13C-NMR and mass spectral (MS) analyses and detected their α-glucosidase inhibitory activity by micro-plate. Results: Ten phenolic constituents were isolated and identified from the active fraction of S. nepalensis. They were identified as isorhamnetin(1), quercetin(2), isorhamnetin-3-O-β-D-glucopyranoside(3), isoquercetin (4), astragalin(5),isorhamnetin-3-O-(6"-p-coumaroyl)-β-D-glucopyranoside(6),isorhamnetin-3-O-(6"-caffeoyl)-β-D-glucopyranoside(7), isoferulic acid(8) Caffeic acid(9) and ellagic acid(10). All of the phenolic compounds were assayed for their hypoglycemic activity against α-glucosidase in vitro. Compound 4, 6 and 7 showed promising α-glucosidase inhibitory activity with the IC50 values of 0.69 mg/ml, 0.56 mg/ml, 0.45 mg/ml, respectively.Conclusion: Compounds 5-8 were isolated for the first time from S. nepalensis. This is the first report on the characterization of phenolic compounds and possible utilization of S. nepalensis for therapeutic intervention in type 2 diabetes.